METHOD OF FILTRATION OF NATURAL HINDRANCES STUDYING TECTONOMAGNETIC FIELD (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
The study of tectonomagnetic field is possible if from the general variations of geomagnetic field could be distinguished a component containing information about the elastic-mechanical strains acting on the earth crust. In general variations of geomagnetic field the main role are playing secular and solar daily variations, the amplitudes of which are comparable with the amplitudes of tectonomagnetic field. On this base the necessity of filtration of above mentioned from general variations arises, the method of which is produced in the present work.
Keywords: induction component; elastic-mechanical strains; solar-diurnal variations; earth crust